A British Ophthalmological Surveillance Unit (BOSU) study into dysthyroid optic neuropathy in the United Kingdom. (October 2018) - Wong, Yun; Dickinson, Jane; Perros, Petros; Dayan, Colin; Veeramani, Pratibha; Morris, Daniel; Foot, Barny; Clarke, Lucy
Abstract This prospective British Ophthalmological Surveillance Unit (BOSU) study on dysthyroid optic neuropathy (DON) determines the incidence, presenting features and management throughout the UK. New cases were identified through the BOSU yellow card and an initial questionnaire and a subsequent 9-month follow-up questionnaire were posted out. From August 2015 to August 2016 DON was reported in 49 patients with 71 eyes affected, 22 patients had bilateral DON. The most common presenting symptom was blurred vision (83%) and the most common examination finding was upgaze restriction (85%). 85% of patients were initially treated with 3 days of either 1 g or 500 mg intravenous methyl prednisolone. We received 25 follow-up questionnaires (51% of the initial cohort) with 38 eyes treated for DON and 13 bilateral cases. The average steroid dose over 9 months was 4.5 g and 47% of patients had a surgical orbital decompression. The mean visual acuity gain after 9 months of follow-up for all patients was 0.25 LogMAR. The mean visual acuity gain after just medical therapy was 0.25 LogMAR and after both medical therapy and orbital decompression it was 0.24 LogMAR. In conclusion, the incidence of DON in the UK from this study is 0.75 per million population per annum. The majority of patients are treated with initial medical therapy and almost half of all patients subsequently went on to have an orbital decompression. With either medical therapy or medical and surgical therapy, vision can improve in patients with DON.